Development of an Experimental Routine for Electrochemical and Laser-Induced Breakdown Spectroscopy Composition Measurements of SmCl3 in LiCl-KCl Eutectic Salt Systems. (3rd July 2019) - Andrews, Hunter; Phongikaroon, Supathorn
Abstract: Four different concentrations of SmCl3 in LiCl-KCl were tested using cyclic voltammetry to determine the diffusion coefficients of Sm(III) and Sm(II) found to be 8.59 × 10 −6 ± 1.67 × 10 −6 and 8.01 × 10 −6 ± 0.98 × 10 −6 cm 2 s −1, respectively. Ten samples, in the form of salt ingots with SmCl3 concentrations ranging from 0.5 to 10.0 wt% were used for the creation of three laser-induced breakdown spectroscopy (LIBS) calibration models corresponding to 484.4-, 490.5-, and 546.7-nm peaks. Results show that the 490.5-nm peak model had the lowest limit of detection at 0.510 wt%, and all three models had similar root-mean-square errors of calibration values ranging from 0.470 to 0.498 wt%. Four validation samples were then used to test the diffusion and LIBS methods' ability to estimate concentration. The results of both methods match well with the inductively coupled plasma mass spectroscopy–measured concentrations.